Ultra-Robust Flexible Electronics by Laser-Driven Polymer-Nanomaterials Integration; Advanced Functional Materials; Vol. 31, iss. 17 - Rodriguez (Rodriges) Contreras R. D. Raul David; Shchadenko S. V. Sergey Vladimirovich; Murastov G. V. Gennadiy Viktorovich; Lipovka A. A. Anna Anatolyevna; Fatkullin M. I. Maksim Ilgizovich; Petrov I. S. Iljya Sergeevich; Tran Tuan Hoang; Khalelov A. A. Alimzhan Alikzhanovich; Saqib M. Muhammad; Villa Pineda N. E. Nelson Enrrique; Bogoslovsky V. Vladimir; Wang Yan; et al. (2021, 2021)
Title screen